I need help on this It’s changing forms of Quadratics ( use distribution and combining like terms to change from vertex form to standard form :)
![I need help on this Its changing forms of Quadratics use distribution and combining like terms to change from vertex form to standard form class=](https://us-static.z-dn.net/files/dad/01bad9b95f6c5d2ccd50dc41b26f6a58.png)
y = ( x-1)^2 +5
FOIL ( x-1)^2 ( x-1)(x-1)
first x*x = x^2
outer x * -1 = -x
inner -1 *x = -x
last -1 *-1 = 1
Add them together
x^2 -x -x+1 = x^2 -2x+1
Replace (x-1)^2 with x^2 -2x+1
y = x^2 -2x+1 +5
= x^2 -2x +6
The answer
y = x^2 -2x+6